Developing resilience among Chinese and Iranian EFL teachers: A multi-dimensional cross-cultural study - Wang, Yongliang; Derakhshan, Ali; Rahimpour, Hadi (Journal of multilingual and multicultural development, 2024)
With the emergence of the positive psychology trend, studying teacher resilience has gained tremendous momentum in mainstream education. Nonetheless, it has yet remained an underappreciated concept in English language education and research. The challenges that teachers experience in maintaining their resilience have also been the focus of a limited number of inquiries. To address these gaps, the present investigation set out to explore the challenges of sustaining resilience among Chinese and Iranian EFL teachers. In doing so, an open-ended questionnaire was administered to 18 Chinese and 15 Iranian EFL teachers, varying in age from 30 to 55 years old. Adopting a qualitative model of data analysis, the participants' responses to the open-ended questionnaire were analyzed through MAXQDA software. The analysis of Chinese and Iranian EFL teachers' answers resulted in the generation of 16 themes and 50 subthemes, demonstrating the challenges to teacher resilience. Findings indicated that both Chinese and Iranian EFL teachers perceived person-focused factors to be the major challenges of preserving teacher resilience. Other factors, including system-focused, context-focused, and process-focused factors, were conceived to be less problematic for teacher resilience. Finally, some major implications of the findings are presented and thoroughly discussed.